The growth effects of R&D spending in the EU: A meta-analysis - Ari Kokko; Patrik Gustavsson Tingvall; Josefin Videnord (Kiel Institute for the World Economy (IfW), 2015)
In this paper the authors conduct a meta-analysis to examine the link between R&D spending and economic growth in the EU and other regions. The results suggest that the growth-enhancing effect of R&D in the EU15 countries does not differ from that in other countries in general, but it is less significant than that for other industrialized countries. A closer inspection of the data reveals that the weak results for the EU15 stem from comparisons with the US - the US has been able to generate a stronger growth response from its R&D spending. Possible explanations for the US advantage include higher private sector investment in R&D and stronger public-private sector linkages than in the EU. Hence, to reduce the "innovation gap" vis-à-vis the US, it may not be enough for the EU to raise the share of R&D expenditures in GDP: continuous improvements in the European innovation system will also be needed, with focus on areas like private sector R&D and public-private sector linkages.
Keywords: F43; O51; O52; 330; meta-analysis; R&D; European Union; EU15; USA; economic growth